Relationship of relative humidity to productivity at a Malaysian electronics industry / Ahmad Rasdan Ismail ... [et al.] (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
The objective of this study is to determine the effects of humidity on the operators' productivity at Malaysian electronic industry. One electronic components assembly factory had been chosen as a subject for the study. The subjects were workers at the assembly section of the factory. The environment examined was the relative humidity (%) of the surrounding workstation area. Two sets of representative data, the relative humidity (%) and production rate were collected during the study. The production rate data for certain sequence period of time were calculated while the relative humidity (%) was measured using BABUC equipment. The correlation and linear regression analysis were conducted in order to obtain the relationship between the effects of relative humidity (%) and the worker productivity. The results from the correlation analysis revealed that there is a linear relationship between the relative humidity (%) and productivity of the workers. The linear regression analysis further reveals that there is a linear equation model with positive slope to describe the relationship of relative humidity (%) and workers productivity for the assembly section involved. The linear regression line obtained is Y = 2.5863X - 28.896.